Tuberculous Dactylitis in a Case of Multiple Scrofuloderma - Sri Linuwih S.W. Menaldi; Farah Faulin Lubis; Jhauharina Rizki Fadhilla; Sandra Widaty (Karger Publishers, 2022)
This paper reports a case of tuberculous dactylitis and multiple scrofuloderma spreading through the lymph nodes. Scrofuloderma, also known as tuberculosis colliquativa cutis, is a form of cutaneous tuberculosis (TB) that occurs most often in children and young adults and involves the skin over the infection focus (i.e., lymph nodes, bones, or joints). Scrofuloderma can affect the lower limbs and upper arms by spreading osteomyelitis TB on the humerus, wrist, and elbow. This study reports the case of a 19-year-old man who initially developed painful and swollen skin, followed by the appearance of numerous recurring lumps on the left arm and hand and the right foot, as well as the folding right hamstring, over 3 years. The patient had no clinical improvement with antibiotics and excision. Radiography of the left hand showed tuberculous dactylitis. A biopsy of the left arm was performed, and Ziehl-Neelsen staining showed acid-fast bacilli. Mycobacterium tuberculosis was confirmed by a real-time polymerase chain reaction. Anti-TB drug treatment was initiated with rifampicin, isoniazid, pyrazinamide, and ethambutol, and debridement was performed on the left hand, which resulted in significant improvement of the lesion. Atypical clinical manifestations and unawareness of M. tuberculosis as an underlying disease delayed the diagnosis and treatment of this patient with tuberculous dactylitis and multiple scrofuloderma.